Scaling of Imbibition Front Dynamics in Heterogeneous Porous Media. Issue 14 (16th July 2020) - Bakhshian, Sahar; Murakami, Margaret; Hosseini, Seyyed Abolfazl; Kang, Qinjun
Abstract: We report a quantitative study on the dynamics of countercurrent imbibition in fractured rock samples with the application of CO2 geosequestration, as the rock matrix is saturated with CO2 and brine exists in the adjacent microfracture. Direct pore‐scale simulations of spontaneous and forced imbibition in a three‐dimensional heterogeneous porous matrix enable us to capture the effect of microscopic properties on the imbibition dynamics as these pore‐level descriptions are ignored in the existing coarse‐grained models. We have established new scaling classes for the propagation of the center of mass of the imbibition front and fluid‐fluid interface broadening. It has become evident that the wettability is a major factor which leads to anomalies in these scaling laws. While the governing capillarity under the water‐wet condition induces fast roughening dynamics of the interface, the adverse effect of capillary pressure under the intermediate‐wet condition leads to a damping effect on the imbibition front fluctuations. Plain Language Summary: Countercurrent imbibition, which is a process of fluid absorption in a porous medium, has numerous applications in oil recovery and CO2 storage in fractured reservoir formations. Typically, natural porous media such as geological formations have complex pore space geometries, which lead to a nonuniform advancement of fluid phases during the imbibition process. The purpose of this study is to investigate the effect of complex pore space geometry on the dynamics of a rough interface between two fluid phases during the imbibition. Using extensive fluid flow simulations, we show the pattern of fluid imbibition in natural rock samples. Besides, we present a new formulation for describing the propagation of imbibed flow as well as the temporal growth of fluid‐fluid interface during the imbibition in real rock samples. Key Points: We present a quantitative analysis of spontaneous and forced imbibition dynamics in a fractured rock acquired from micro‐CT images We establish a new scaling law characterizing the dynamics of fluid‐fluid interface growth during the imbibition We study the effect of wettability on the scaling dynamics of interface roughness during the countercurrent imbibition